Development and application of flavor enhancer ingredient from shiitake mushroom (Lentinula edodes) byproducts - Padermo, Samara dos Santos Harada (2021)
The reduction of sodium consumption is one of the current concerns, since the high intake of this micronutrient can lead to the development of cardiovascular problems and hypertension. Concomitant to this, the demand for food with less/ or without the addition of synthetic additives, in line with the clean label movement, is growing. Given this panorama, it is necessary to search for new natural ingredients that have the potential to replace or reduce the use of conventional additives in foods. The use of mushrooms as flavor enhancers in formulations with sodium reduction has been researched. However, studies focused on the use of byproducts from mushrooms production (stipes), with this same objective, are still scarce. Thus, this study aimed to develop a powder ingredient rich in umami compounds, obtained from shiitake mushroom (Lentinula edodes) byproducts. To optimize the umami compounds extraction process, the Response Surface Methodology and hot-air dried shiitake stipes were used. The Central Composite Rotatable Design was applied with two independent variables (solute:solvent ratio (w:v) and extraction temperature), with the umami taste intensity evaluated by a sensory panel as a dependent variable. The solute:solvent ratio had effect on the umami taste intensity of the extracts, as opposed to temperature. From the optimized extraction condition, the effect of the dehydration method (hot-air drying and freeze-drying) applied to the shiitake stipes prior to the extraction of umami compounds was evaluated. The main umami compounds (free amino acids and 5\'-nucleotides) were evaluated by high performance liquid chromatographic. From the chemical composition, the Equivalent Umami Concentration was calculated, evidencing that hot-air drying favored greater recovery of umami compounds when compared to freeze drying. The liquid extract produced under the optimized conditions (1:20 solute:solvent ratio (w:v), 30 min, regardless the temperature), from stipes dehydrated by hot-air drying, was used to produce the powder ingredient by spray drying. The obtained ingredient (Umami Ingredient) had a light color, high water solubility, low sodium (83,52 mg Na/100g) and moisture content (2.76%), in addition to present high glutamic acid retention (97%). In order to verify the potential of the Umami Ingredient as a flavor enhancer in food with reduced sodium content, as well as its impact on technological properties, the ingredient was applied in corn extruded snacks and also in beef burgers with low-sodium content. In the sensory evaluation of the extruded snacks, the Umami Ingredient (1 and 1.5%) presented similar results to those of the sample added of monosodium glutamate (MSG) for the attributes seasoning flavor, salty taste and umami taste; in addition to not having affected the physical properties (density and cutting force) of the snacks. The physicochemical and instrumental texture properties of the beef burgers were evaluated. The tested formulations (1 and 2% of Umami Ingredient) presented a minimum impact on the technological properties of the burgers (little changes in color, pH, aw, and cohesiveness in some treatments). Thus, the Umami Ingredient proved to be a potential alternative to replace MSG in food with reduced sodium content, acting as a flavor enhancer and reducing the use of additives in products formulations. Also, the new ingredient proposal contributes to the use of agro-industrial residue, adds value to this byproduct, in addition to meeting the consumer market demand for natural additives.